Optical beam transport to a remote location for low jitter pump-probe experiments with a free electron laser - P. Cinquegrana; S. Cleva; A. Demidovich; G. Gaio; R. Ivanov; G. Kurdi; I. Nikolov; P. Sigalotti; M. B. Danailov (Physical Review Special Topics. Accelerators and Beams, 2014)
In this paper we propose a scheme that allows a strong reduction of the timing jitter between the pulses of a free electron laser (FEL) and external laser pulses delivered simultaneously at the FEL experimental stations for pump-probe–type experiments. The technique, applicable to all seeding-based FEL schemes, relies on the free-space optical transport of a portion of the seed laser pulse from its optical table to the experimental stations. The results presented here demonstrate that a carefully designed laser beam transport, incorporating also a transverse beam position stabilization, allows one to keep the timing fluctuations, added by as much as 150 m of free space propagation and a number of beam folding mirrors, to less than 4 femtoseconds rms. By its nature our scheme removes the major common timing jitter sources, so the overall jitter in pump-probe measurements done in this way will be below 10 fs (with a margin to be lowered to below 5 fs), much better than the best results reported previously in the literature amounting to 33 fs rms.